IMPLEMENTASI STRATEGI PEMBELAJARAN INKUIRI PADA PEMBELAJARAN PAI DI KELAS VII SMP NU GONDANGLEGI - Achadah, Alif; Apriani, Mistia (PRODI PAI FIK UNIRA MALANG, 2022)
Learning Islamic religious education is an important education for the human environment. It is also important to instill Islamic values that come from God Almighty to humans. Islamic religious education learning in schools provides teaching materials and keeps students trained in education and learning so that teachers can educate their students to achieve the expected vision, mission and goals. This study aims to explore